Inclusion of exogenous enzymes in feedlot cattle diets: Impacts on physiology, rumen fermentation, digestibility and fatty acid profile in rumen and meat - Alexandre L. Simon; Priscila M. Copetti; Rafael V.P. Lago; Maksuel G. Vitt; Aline L. Nascimento; Luiz Eduardo Lobo e Silva; Roger Wagner; Bruna Klein; Camila Soares Martins; Gilberto V. Kozloski; Aleksandro S. Da Silva (Biotechnology Reports, 2024)
The objective of this study was to evaluate if the inclusion of a blend composed of exogenous enzymes (amylase, protease, cellulase, xylanase and beta glucanase) in the individual and combined form in the feedlot steers diet has benefits on the physiology, rumen fermentation, digestibility and fatty acid profile in rumen and meat. The experiment used 24 animals, divided into 4 treatments, described as: T1-CON, T2-BLEND (0.5 g mixture of enzyme), T3-AMIL (0.5 g alpha-amylase), T4-BLEND+AMIL (0.5 g enzyme blend+ 0.5 g amylase). The concentration of mineral matter was higher in the meat of cattle of T4-BLEND+AMIL. A higher proportion of monounsaturated fatty acids was observed in the T3-AMIL group when compared to the others. The percentage of polyunsaturated fatty acids was higher in the T2-BLEND and T4-BLEND+AMIL compared to the T1-CON. The combination of exogenous enzymes in the diet positively modulate nutritional biomarkers, in addition to benefits in the lipid and oxidative profile meat.